The multidimensional poverty index and multi-criteria analysis. The case of Ecuador 2009-2018 - Guallichico, Lesly (2021)
Economics in its formation was based on utilitarian ethics, deriving in pragmatic economic models that deviated from the effective satisfaction of collective human needs towards strictly economic and mercantile individual well-being, a fact for which neoclassical economics defines well-being as “ the satisfaction of preconceived needs as unlimited in a world of limited resources ”(Valencia and Cuervo, 1999). After this, the theory of "consumer supremacy" is developed, considering that the individual increases his well-being when he increases his consumption, in other words, more money, greater utility and therefore greater happiness.